A semi-covalent molecularly imprinted fluorescent sensor for highly specific recognition and optosensing of bisphenol A. Issue 1 (15th December 2020) - Zhang, Jinna; Wang, Haiyang; Xu, Longhua; Xu, Zhixiang
Abstract : A novel mesoporous fluorescent molecularly imprinted sensor for selective detection of bisphenol A (BPA) in food materials was fabricated via a semi-covalent imprinting method. Abstract : A novel mesoporous fluorescent molecularly imprinted sensor for selective detection of bisphenol A (BPA) in food materials was fabricated via a semi-covalent imprinting method. The imprinting precursor that served as an alternative template molecule for BPA was prepared via thermally reversible isocyanate bonding, which effectively improved the imprinting efficiency for the molecularly imprinted sensor. Carbon dots (CDs) were embedded in mesoporous silica as signal recognition elements that exhibited quenching upon BPA binding. Subsequently, through the sol–gel process, the molecularly imprinted layer was coated on the CDs silica layer and provided specific recognition sites for BPA. The composite of CDs embedded in the mesoporous molecularly imprinted polymer (CDs@MIP) was characterized with scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller measurements and thermogravimetric analysis. The mechanism of carbon dots quenching and the high selectivity of CDs@MIP towards BPA were explored. The linear response range of the sensor was from 0.025 mg L −1 to 2 mg L −1 with a limit of detection of 0.016 mg L −1 . The method was successfully applied for the determination of food samples and recoveries ranged from 92.5% to 101.1%. The BPA contents in actual samples were determined using high performance liquid chromatography and the proposed sensor, showing no significant difference between the two methods.